Preparation method and application of microcrystalline cellulose composite preservative for natural latex
By using microcrystalline cellulose composite preservative agent (CNCs/TA/Ag) in natural latex, the problems of natural latex spoilage and irritating odor of existing preservatives are solved, and effective antibacterial properties and environmentally friendly latex preservation effect are achieved.
Patent Information
- Application Number
- CN202411756220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
Natural latex is prone to spoilage because it contains nutrients needed by bacteria. Existing preservatives such as ammonia water have problems such as irritating odors, corrosiveness and increasing production costs.
Microcrystalline cellulose (CNCs) are used as carrier and dispersant, tannin acid (TA) is coated through hydrogen bonding, chelated with silver ions (Ag+), and in situ reduction is used for plant polysaccharides to prepare an ammonia-free natural latex preservative agent (CNCs/TA/Ag) composite material.
This preservative has strong antibacterial properties for a variety of microorganisms, effectively prevents latex from deteriorating, improves shelf life, and has no irritating odors, is environmentally friendly, and can enhance the mechanical properties of rubber products.
Smart Images

Figure BDA0005166354580000091 
Figure HDA0005166354600000011 
Figure HDA0005166354600000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of natural latex preservatives, and in particular relates to a preparation method of a microcrystalline cellulose composite preservative for natural latex and application thereof. Background Art
[0002] Natural rubber latex (NRL) is a natural polymer material obtained through biosynthesis from the Brazilian Hevea brasiliensis tree. Its main component is rubber hydrocarbon, which is biopolymerized from cis-1,4-isoprene monomers. Its chemical structure is (C5H8) n Natural rubber has become irreplaceable to synthetic rubber and other materials due to its excellent comprehensive properties, such as high elasticity, high strength, high elongation, wear resistance, tear resistance, impact resistance, oil resistance, corrosion resistance, as well as excellent insulation, sealing, flexibility, and adhesion. It is widely used in industry, agriculture, national defense, transportation, machinery manufacturing, medicine and health, and daily life.
[0003] However, fresh latex contains a lot of sugars, proteins, phosphates and other "nutrients" needed by bacteria, so it is very easy to deteriorate due to the action of bacteria. According to experiments, under normal rubber tapping conditions, the number of bacteria in the rubber cup can reach 8×10 6 / mL latex, and reproduce very quickly, which changes the shape of latex, reduces the stability of latex, and accelerates the natural coagulation speed of latex. At the same time, sugars will also be absorbed and utilized by bacteria, converted into various acids, which will also cause latex to coagulate. Proteins will also be decomposed into amino acids by enzymes secreted by bacteria for absorption and utilization, and excess NH3, H2S, etc. will be excreted from the body, causing the deteriorated latex to emit a rancid smell, thus affecting the rubber making process, product quality and economic benefits. The losses caused by the deterioration of fresh milk due to microbial action are quite huge every year. Therefore, maintaining the stability of natural latex is crucial to the primary processing and application of natural rubber.
[0004] For a long time, a lot of research and experiments have been conducted on the preservation of natural latex at home and abroad, and a variety of latex preservatives have been developed, among which ammonia water is the most widely used, and there are also sodium sulfite, formaldehyde, urea, inorganic alkali, hydroxylamine, etc., which can be used alone or in combination with ammonia, such as NH3+SDC / ZnO (SDC: sodium diethyldithiocarbamate, ZnO: zinc oxide), NH3+ZDC / ZnO (ZDC: zinc diethyldithiocarbamate), NH3+TT / Zn O (TT: tetramethylthiuram disulfide), NH3+HH (HH: hydrated hydrazine), etc. However, ammonia is volatile, produces irritating odor, is corrosive, deteriorates the working environment, causes harm to the human body, and increases the amount of acid used for latex coagulation in the later stage, increasing production costs.
[0005] Based on this, the present invention uses microcrystalline cellulose (CNCs) as a carrier and dispersant, coats tannic acid (TA) on the surface of microcrystalline cellulose through hydrogen bonding, and then utilizes the phenolic hydroxyl groups on the tannic acid molecules to bind to silver ions (Ag + ) are chelated by self-assembly, and then reduced in situ by plant polysaccharides to obtain a preservative (CNCs / TA / Ag) composite material for ammonia-free latex. Since the tannic acid and nanosilver in the preservative have strong antibacterial properties against a variety of microorganisms (such as bacteria, fungi and viruses, etc.), the synergistic effect of the two has a good antibacterial property for fresh latex, prevents latex from deteriorating, and improves its shelf life. It can also overcome the shortcomings of ammonia-based broad-spectrum antibacterial agents in the preservation of natural latex, such as irritating odor and corrosiveness. At the same time, the rod-like structure of microcrystalline cellulose has a reinforcing effect on latex and can improve the mechanical properties of rubber products. At present, there is no relevant literature report on the application of CNCs / TA / Ag composite materials as preservatives in the preservation of fresh natural latex. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the existing preservatives for natural latex, the present invention provides a method for preparing a microcrystalline cellulose composite preservative for natural latex. The method has a simple preparation process, and the prepared microcrystalline cellulose composite preservative for natural latex can effectively improve the shelf life of fresh natural latex. The specific technical scheme is as follows.
[0007] A method for preparing a microcrystalline cellulose composite preservative for natural latex is mainly achieved through the following technical solutions:
[0008] (1) Preparation method of microcrystalline cellulose (CNCs)
[0009] 1-2 cm plant fiber is soaked in NaOH solution for 24-48 hours, then heated to 100°C and boiled for 1-2 hours, filtered, washed with deionized water until neutral, and placed in a blast drying oven at 60°C to dry to constant weight; the dried fiber is placed in nitric acid and glacial acetic acid aqueous solution and boiled for 2-4 hours, the obtained white fiber powder is filtered and washed until neutral, then placed in a blast drying oven at 60°C to dry to constant weight, and finally the dried white fiber powder is crushed with a high-speed grinder (about 7000r / min) to obtain CNCs.
[0010] (2) Preparation method of microcrystalline cellulose composite preservative (CNCs / TA / Ag)
[0011] 2-8g CNCs and 0.4-1.5L TA aqueous solution (concentration of 10g / L, pH=3.5-6.5) were stirred and mixed at room temperature for 8-12h, and then NaOH solution was added to the solution until it was neutral. The mixed solution was heated to 50-70℃, and 20-80g plant polysaccharide aqueous solution (mass fraction of 2%) was added and stirred for 10-30min; after the temperature stabilized, 0.05-1g AgNO3 was added and stirred for 1-3h; after the reaction was completed, the filter cake was filtered, and the filter cake was washed with deionized water to remove impurities, and dried in a vacuum oven at 60℃ to constant weight to obtain a CNCs / TA / Ag composite preservative.
[0012] The invention uses microcrystalline cellulose as a carrier and a dispersant, assembles and coats tannic acid on the surface of microcrystalline cellulose through hydrogen bonding, utilizes the phenolic hydroxyl groups on the tannic acid molecules to chelate with silver ions through self-assembly, and then uses plant polysaccharide in-situ reduction to prepare an ammonia-free natural latex preservative. The preservative has a good preservation effect on fresh latex, has no irritating odor, and is environmentally friendly.
[0013] As a preferred embodiment of the above technical solution, the plant fiber in step (1) is one or a combination of bagasse, sisal fiber, wood fiber, cotton fiber, bamboo fiber or stem fiber of other grass plants.
[0014] As a preferred embodiment of the above technical solution, the NaOH content in the NaOH aqueous solution in step (1) is 5 to 20 wt%.
[0015] As a preferred embodiment of the above technical solution, the proportions of nitric acid and glacial acetic acid in the nitric acid and glacial acetic acid aqueous solutions in step (1) are 5-10wt% and 20-50wt% respectively.
[0016] As a preferred embodiment of the above technical solution, the plant polysaccharide in step (2) can be selected from okra polysaccharide, aloe polysaccharide, yam polysaccharide, peach gum polysaccharide, etc., or a combination of several of them.
[0017] A microcrystalline cellulose composite preservative for natural rubber latex is prepared by the above-mentioned preparation method.
[0018] The application of the above-mentioned microcrystalline cellulose composite preservative for natural latex in the storage of fresh natural latex.
[0019] As a preferred embodiment of the above application, the preparation of fresh natural latex storage specifically includes: taking natural latex, then adding 0.01-0.05% of the weight of natural latex microcrystalline cellulose composite preservative, stirring and blending evenly, and then standing in an open environment, observing and recording every 24 hours.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The method for preparing the microcrystalline cellulose composite preservative for natural latex of the present invention can prepare a preservative for natural latex with microcrystalline cellulose as a carrier and dispersant, which contains two antibacterial substances, tannic acid and silver nanoparticles, on the surface and has no irritating odor. The preservative has strong antibacterial properties against various microorganisms (such as bacteria, fungi and viruses) in fresh natural latex and can effectively prevent latex from coagulation and deterioration.
[0022] (2) The preparation process of the microcrystalline cellulose composite preservative for natural latex of the present invention is simple, and the main raw materials for preparation are widely available and renewable, which greatly reduces the large-scale production cost and is suitable for industrial-scale production.
[0023] (3) The microcrystalline cellulose composite preservative for natural rubber latex of the present invention has good hydrophilicity, is non-volatile, environmentally friendly, non-irritating, has good stability and does not pollute the environment.
[0024] (4) The cellulose rod-like structure of the microcrystalline cellulose composite preservative for natural latex of the present invention has a reinforcing effect on latex and can improve the mechanical properties of rubber products. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 Digital photos of the appearance of CNCs, TA, and CNCs / TA / Ag products.
[0027] Figure 2 The thermal gravimetric test results of CNCs and CNCs / TA / Ag.
[0028] Figure 3 Microscopic morphology of CNC and CNCs / TA / Ag.
[0029] Figure 4 Digital photos of the inhibition zones of CNCs and CNCs / TA / Ag in Staphylococcus aureus and Escherichia coli.
[0030] Figure 5 Digital photos comparing the preservation effects of CNCs / TA / Ag preservative and blank CNCs on natural latex in Example 1. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.
[0032] The main raw materials used in the following examples are: bagasse (industrial grade), silver nitrate (chemically pure), sodium hydroxide (chemically pure), tannic acid (industrial grade), okra polysaccharide (industrial grade), nitric acid (chemically pure), and glacial acetic acid (chemically pure).
[0033] Embodiment 1:
[0034] A method for preparing a microcrystalline cellulose composite preservative for natural latex comprises the following steps:
[0035] (1) Preparation method of microcrystalline cellulose (CNCs)
[0036] 1-2 cm bagasse fibers were soaked in a 5 wt% NaOH solution for 24 h, then heated to 100 °C and boiled for 2 h, filtered, washed with deionized water until neutral, and dried in a blast drying oven at 60 °C to constant weight; the dried fibers were placed in an aqueous solution of 10 wt% nitric acid and 50 wt% glacial acetic acid, respectively, and boiled for 2 h. The obtained white fiber powder was filtered and washed until neutral, then placed in a blast drying oven at 60 °C to constant weight, and finally the dried white fiber powder was crushed with a high-speed grinder (about 7000 r / min) to obtain CNCs.
[0037] (2) Preparation method of microcrystalline cellulose composite preservative (CNCs / TA / Ag)
[0038] 2g CNCs and 0.4L TA aqueous solution (concentration of 10g / L, pH=3.5) were stirred and mixed at room temperature for 8h, and then NaOH solution was added to the solution until it was neutral. The mixed solution was heated to 50℃, and 20g okra polysaccharide aqueous solution (mass fraction of 2%) was added and stirred for 10min; after the temperature stabilized, 0.05g AgNO3 was added and stirred for 1h; after the reaction was completed, the filter cake was filtered, and the filter cake was washed with deionized water to remove impurities, and dried in a vacuum oven at 60℃ to constant weight to obtain a CNCs / TA / Ag composite preservative.
[0039] This embodiment also provides an application of a microcrystalline cellulose composite preservative for natural latex in the storage of fresh natural latex, comprising the following steps: taking fresh natural latex, then adding 0.05% of the weight of the natural latex microcrystalline cellulose composite preservative for natural latex, stirring and blending evenly, and then standing in an open environment, observing and recording once every 24 hours. The observation results are shown in Table 1.
[0040] Embodiment 2:
[0041] A method for preparing a microcrystalline cellulose composite preservative for natural latex comprises the following steps:
[0042] (1) Preparation method of microcrystalline cellulose (CNCs)
[0043] 1-2 cm bagasse fibers were soaked in a 20 wt% NaOH solution for 24 h, then heated to 100 °C and boiled for 1 h, filtered, washed with deionized water until neutral, and dried in a blast drying oven at 60 °C to constant weight; the dried fibers were placed in an aqueous solution of 10 wt% nitric acid and 50 wt% glacial acetic acid, respectively, and boiled for 2 h. The obtained white fiber powder was filtered and washed until neutral, then placed in a blast drying oven at 60 °C to constant weight, and finally the dried white fiber powder was crushed with a high-speed grinder (about 7000 r / min) to obtain CNCs.
[0044] (2) Preparation method of microcrystalline cellulose composite preservative (CNCs / TA / Ag)
[0045] 8g CNCs and 1.5L TA aqueous solution (concentration of 10g / L, pH=6.5) were stirred and blended at room temperature for 12h, and then NaOH solution was added to the solution until it was neutral. The mixed solution was heated to 80℃, and 80g okra polysaccharide aqueous solution (mass fraction of 2%) was added and stirred for 30min; after the temperature stabilized, 1g AgNO3 was added and stirred for 3h; after the reaction was completed, the filter cake was filtered, and the filter cake was washed with deionized water to remove impurities, and dried in a vacuum oven at 60℃ to constant weight to obtain a CNCs / TA / Ag composite preservative.
[0046] This embodiment also provides an application of a microcrystalline cellulose composite preservative for natural latex in the storage of fresh natural latex, comprising the following steps: taking fresh natural latex, then adding 0.01% of the weight of the natural latex microcrystalline cellulose composite preservative for natural latex, stirring and blending evenly, and then standing in an open environment, observing and recording once every 24 hours. The observation results are shown in Table 1.
[0047] Embodiment 3:
[0048] A method for preparing a microcrystalline cellulose composite preservative for natural latex comprises the following steps:
[0049] (1) Preparation method of microcrystalline cellulose (CNCs)
[0050] 1-2 cm bagasse fibers were soaked in a 10 wt% NaOH solution for 36 h, then heated to 100 °C and boiled for 1.5 h, filtered, washed with deionized water until neutral, and dried in a blast drying oven at 60 °C to constant weight; the dried fibers were placed in an aqueous solution of 7 wt% and 40 wt% nitric acid and glacial acetic acid, respectively, and boiled for 3 h. The obtained white fiber powder was filtered and washed until neutral, then placed in a blast drying oven at 60 °C to constant weight, and finally the dried white fiber powder was crushed with a high-speed grinder (about 7000 r / min) to obtain CNCs.
[0051] (2) Preparation method of microcrystalline cellulose composite preservative (CNCs / TA / Ag)
[0052] 4g CNCs and 0.8L TA aqueous solution (concentration of 10g / L, pH = 4) were stirred and blended at room temperature for 10h, and then NaOH solution was added to the solution until it was neutral. The mixed solution was heated to 60°C, and 60g okra polysaccharide aqueous solution (mass fraction of 2%) was added and stirred for 20min; after the temperature stabilized, 0.5g AgNO3 was added and stirred for 2h; after the reaction was completed, the filter cake was filtered, and the filter cake was washed with deionized water to remove impurities, and dried in a vacuum oven at 60°C to constant weight to obtain a CNCs / TA / Ag composite preservative.
[0053] This embodiment also provides an application of a microcrystalline cellulose composite preservative for natural latex in the storage of fresh natural latex, comprising the following steps: taking fresh natural latex, then adding 0.025% of the natural latex weight of the microcrystalline cellulose composite preservative for natural latex, stirring and blending evenly, and then standing in an open environment, observing and recording once every 24 hours. The observation results are shown in Table 1.
[0054] Table 1 Comparison of the preservation effect of CNCs and Example CNCs / TA / Ag on fresh latex
[0055]
[0056]
[0057] The above are only preferred embodiments of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principles of the present invention. These improvements should also be regarded as within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a microcrystalline cellulose composite preservative for natural rubber latex, characterized in that The specific steps are: (1) Preparation method of microcrystalline cellulose (CNCs) 1-2 cm plant fiber is soaked in NaOH solution for 24-48 hours, then heated to 100°C and boiled for 1-2 hours, filtered, washed with deionized water until neutral, and placed in a blast drying oven at 60°C to dry to constant weight; the dried fiber is placed in nitric acid and glacial acetic acid aqueous solution and boiled for 2-4 hours, the obtained white fiber powder is filtered and washed until neutral, then placed in a blast drying oven at 60°C to dry to constant weight, and finally the dried white fiber powder is crushed with a high-speed grinder (about 7000r / min) to obtain CNCs. (2) Preparation method of microcrystalline cellulose composite preservative (CNCs / TA / Ag) 2-8g CNCs and 0.4-1.5L TA aqueous solution (concentration of 10g / L, pH=3.5-6.5) were stirred and mixed at room temperature for 8-12h, and then NaOH solution was added to the solution until it was neutral. The mixed solution was heated to 50-70℃, and 20-80g plant polysaccharide aqueous solution (mass fraction of 2%) was added and stirred for 10-30min; after the temperature stabilized, 0.05-1g AgNO3 was added and stirred for 1-3h; after the reaction was completed, the filter cake was filtered, and the filter cake was washed with deionized water to remove impurities, and dried in a vacuum oven at 60℃ to constant weight to obtain a CNCs / TA / Ag composite preservative.
2. The method according to claim 1, characterized in that The plant fiber in step (1) is one or a combination of bagasse, sisal fiber, wood fiber, cotton fiber, bamboo fiber or stem fiber of other grass plants.
3. The method according to claim 1, characterized in that The NaOH aqueous solution in step (1) contains 5 to 20 wt % NaOH.
4. The method according to claim 1, characterized in that: In the aqueous solution of nitric acid and glacial acetic acid in step (1), the proportions of nitric acid and glacial acetic acid are 5-10wt% and 20-50wt% respectively.
5. The method according to claim 1, characterized in that The plant polysaccharide in step (2) can be selected from okra polysaccharide, aloe polysaccharide, yam polysaccharide, peach gum polysaccharide and the like, or a combination of several of the above plant polysaccharides.
6. A microcrystalline cellulose composite preservative for natural rubber latex, characterized in that: The microcrystalline cellulose composite preservative for natural latex is prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the microcrystalline cellulose composite preservative for natural latex as claimed in claim 6 in the storage of fresh natural latex.
8. The use according to claim 7, characterized in that: The preparation and storage of fresh natural latex specifically includes: taking fresh natural latex, then adding 0.01-0.05% of the weight of natural latex microcrystalline cellulose composite preservative, stirring and blending evenly, and then standing in an open environment, observing and recording once every 24 hours.